Identification of Serum-Based Metabolic Feature and Characteristic Metabolites in Paraquat Intoxicated Mouse Models - Yu, Youjia; Gao, Zishan; Lou, Jiaqian; Mao, Zhengsheng; Li, Kai; Chu, Chunyan; Hu, Li; Li, Zheng; Deng, Chuwei; Fan, Hanting; Chen, Peng; Huang, Huijie; et al. (Frontiers in Physiology, 2020)
Paraquat (PQ) is a widely used herbicide which can cause high mortality to humans. However, relatively few studies focus on metabolic feature of PQ intoxication for investigating the underlying mechanisms. Here we performed non-targeted metabolomics profiling of serum samples from acute and chronic PQ intoxicated mouse models by gas chromatography time-of-flight mass spectrometry (GC-TOF/MS) to identify metabolic feature and characteristic metabolites of acute and chronic PQ intoxication. Results showed that, 3-indolepropionic acid (IPA) and pathway of glycine, serine and threonine metabolism were significantly altered after acute PQ intoxication; 2-hydroxybutyric acid and the ratio of L-serine/glycine were of significance between acute and chronic PQ intoxication. Then targeted metabolomics profiling was conducted by liquid chromatography-mass spectrometry (LC-MS) analysis to confirm the changes of IPA after acute PQ intoxication. Moreover, IPA-producing gut bacteria in feces were quantified by qRT-PCR to explain the varied IPA serum concentration. Clostridium botulinum and Peptostreptococcus anaerobius were significantly suppressed after acute PQ intoxication. The data suggested that PQ caused oxidative damage partially though suppression of anti-oxidative metabolite producing gut bacteria. In conclusion, we indentified characteristic metabolites and pathway of acute and chronic PQ intoxication which could be potential biomarkers and therapeutic targets.